Combatting corruption at the grassroots level in Nigeria - Oluyitan, Funso E. (Springer International Publishing, 2020)
Contents: Introduction -- Theoretical overview of corruption -- My interview with the oath takers -- Research findings: motives and impacts in oath taking -- Discussion of findings: taking, keeping and violating the oath -- Policy and practical implications for future anti-corruption programs.